Pemanfaatan kulit pisang kepok sebagai ekoenzim untuk pertumbuhan dan produksi selada (Lactuca sativa L) di lahan organosol - Hafiz Irsyad; Fedri Ibnusina; Silfia (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
Lettuce (Lactuca Sativa L) is a horticultural commodity that is in great demand because of its high nutritional content. However, increasing lettuce plant production is often constrained by suboptimal soil conditions, such as organosol soil. One alternative that can be used to increase lettuce growth and production is to use ecoenzymes from kepok banana peels. This study aims to examine the effect of kepok banana peel ecoenzymes on lettuce plant growth and production in organosol soil. This study used the Randomized Block Design (RAD) method with three treatments of ecoenzyme administration at doses of 25 ml/liter, 30 ml/liter, and 35 ml/liter of water, and 9 replications. The results showed that administration of kepok banana peel ecoenzymes at a dose of 25 ml/liter gave the best results in increasing the number of leaves, leaf width, leaf length, crown weight, and root weight of lettuce plants. Although it did not have a significant effect on fresh weight and root length, kepok banana peel ecoenzymes can be an effective alternative to increase lettuce plant growth. Based on these findings, the use of kepok banana peel ecoenzyme at the right dose can increase lettuce cultivation yields in organosol soil, as an alternative to environmentally friendly organic fertilizers.